Communication of Educational Zoning Policy in Makassar City - Herman H; Andi Anugrah Mahyuddin; Amirullah Amirullah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to 1) To examine the communication of the educational zoning policy for the acceptance of new students in the city of Makassar, 2) To describe the implementation of the educational zoning policy for the acceptance of new students in the city of Makassar, 3) To describe the pattern of mass communication in the education zoning policy on the acceptance of participants. new students in Makassar city. This research method uses a qualitative approach with data collection techniques through observation, interviews and documentation. The data analysis technique uses an interactive model, namely data collection, data condensation, data presentation, and verification/conclusion. The results showed that 1) the communication of the educational zoning policy for the acceptance of new students was deemed to be less effective, 2) The implementation of the zoning policy for New Student Admissions is considered less effective, 3) The mass communication pattern in the zoning policy for new student education in Makassar is considered effective. Overall, it can be understood that the communication of education zoning policies in Makassar City is less effective, this is the absence of massive socialization